Evaluation of the Effectiveness E-Government System in the Semarang City Land Office (Importance Performance Analysis Method Approach) - Amalina Nur Azizah; Amie Kusumawardhani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to identify and analyze the dimensional factors of the system evaluation model from system quality, information quality, and service quality to user satisfaction with the Lentera system as a representation of e-government implemented at the Semarang City Land Office. This research tries to do three main identifications, namely whether there is a gap between the assessment of the importance and performance of the Lentera system from the user on each variable attribute that describes user satisfaction. Second, how it is the distribution of each attribute of each variable in the IPA quadrant matrix. Third, how to analyze the recommendations of each attribute of each variable as a form of system evaluation so that improvements to the Lentera system can be made in the future. The data analysis technique used in this research is quantitative research, and the research analysis method uses the importance performance analysis (IPA) approach. By using the Lentera system user as the research sample, 112 respondents were obtained as observation data. The results showed that all the attributes of each variable of system quality, information quality and service quality resulted in a negative gap between performance assessment and importance on the Lentera system, which means that the level of user satisfaction is quite low when using the Lentera system. This is also shown from the distribution of each attribute on each variable in the IPA quadrant matrix, which indicates some attributes need to be improved and some attributes are sufficient to be maintained because they already have a fairly good performance. Overall, this study shows the evaluation of the Lentera system related to the assessment of the importance and performance of system users. From the results of this evaluation, recommendations can be made that the quality of the system, the quality of information, and the quality of services need to be improved on some of its attributes.